Very-low-level U-space Conflict Detection and Resolution: Focused Developments, Analysis, and Future Prospects - Badea, Calin Andrei; Morfin Veytia, Andres; Vidosavljević, Andrija; Ellerbroek, Joost; Hoekstra, Jacco (Journal of Open Aviation Science, 2025)
A safe and efficient integration of U-space operations necessitates robust conflict detection and resolution (CD&R) mechanisms, particularly for very-low-level (VLL) operations in constrained urban airspace. Research has focused on the development of navigation and traffic management concepts suitable for such operations that aim to mitigate the challenges posed by this novel environment. However, the current research landscape is fragmented, with CD&R methods still needing to be integrated within a more unified framework. In this paper, we present an overview of our approach towards air traffic management for VLL U-space operations and analyse their limitations compared to other work. Then, based on the conclusions of other existing work, we identify key areas for improvement and propose recommendations for future research and development for VLL airspace structure design, conflict detection and resolution, and U-space operations simulations. We conclude that a unified approach should be used towards integrating and investigating the interdependencies of U-space services within a standardised verification and validation framework.